Nutrition assessment of school-going children in the rural area of District Swabi, Pakistan - Ullah, Shakir; Islam, Umair; Rahman, Iqbal Khan; Muhammad, Noor; Muhammad, Iqbal; Khan, Hamza; Khan, Abbas; Ali, Basit (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Anemia and malnutrition are global health problem among all nutritional disorder with high morbidity and mortality in school aged children. Therefore the aims of the study assist the prevalence and risk factors of anemia, and malnutrition among school-going children of District Swabi Pakistan. A total of 600 school aged children of aged 4-15 years were included in the study in 2023. Hematocrit level was obtained using a centrifuge microhematocrit, and converted to hemoglobin using standard conversion. Nutritional status was determined by the anthropometric measurements, and demographic characteristics were obtained by questionnaire. Anemia and malnutrition were defined according to the World Health Organization standards. In current research work 600 children were selected for the assessment of nutritional status in which 105(17.5%) were found malnutrated. Moderate frequency of assessment were found among anemia 25(23.80%), stunting 22(21%) and underweight 18(17%) respectively. High frequency was found in malnutrition 40(38%) while very low frequency was seen in wasting 2(1.90%). Gender wise assessment of the students shows that the nutritional deficiencies were slightly high in male as compare to female students in comparison of Anemia, Malnutrition, Stunting, and Underweight and in wasting respectively. Aged group wised assessment of the students shows that the nutritional deficiencies were slightly high in low aged student (4-7 years) as compare to 8-11 years and 12-15 years in both gender. Among them Malnutrition were very high leading by Anemia while Underweight and wasting of very low frequency respectively.